Do We Still Need Carbon-Intensive Capital When Transitioning to a Green Economy? - Wei Jin; Rick van der Ploeg; Lin Zhang (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper presents a two-sector green endogenous growth model to explore a mechanism that explains why carbon-intensive capital is not necessarily shut down during transition to a green economy. Without accumulating clean capital to offset carbon emissions, a tightening of climate regulation leads to the running down of carbon-intensive capital. However, if climate regulations induce stepping-up of carbon-free capital to offset warming damages, the economic value of carbon-intensive capital can be protected and the running down of carbon-intensive assets can be mitigated. The use of carbon-intensive capital gives the economic means to enhance clean capital accumulation and sustain endogenous growth. Both carbon-intensive and carbon-free capital may thus be needed for an efficient transition to green growth.
Keywords: Q54; Q43; Q32; O13; O44; C61; 330; endogenous growth; green growth; two-sector growth model; climate policy